REDESIGN OF THE TRANSFORMATION MODEL OF ISLAMIC LEADERSHIP VALUES IN CHARACTER FORMATION OF STUDENTS AT THE DARUL HASANAH ISLAMIC BOARDING SCHOOL - Rustam Lubis; M. Syukri Azwar Lubis; Muhammad Tohir Ritonga (Jurnal Bilqolam Pendidikan Islam, 2026)
This study examines the urgency of redesigning the model of transformation of Islamic leadership values at Pondok Pesantren Darul Hasanah in facing the currents of globalization and digitalization. The research aims to describe the model that has been applied, analyze the process of value internalization through habituation and student organizations, identify contemporary challenges, and formulate a relevant redesign. A qualitative approach with a case study design was used, employing in-depth interviews, participatory observation, and documentation study, analyzed through the interactive model of Miles, Huberman, and Saldaña and validated through triangulation. The findings show that the traditional model relies on the exemplary conduct of the Nyai (uswah hasanah), habituation (tadrib), and the teaching of classical texts. Value internalization is reinforced through student organizations (OPPP and UKS) as vehicles for authentic leadership practice. The main challenges identified include the influence of digital media, gaps in contextualizing classical materials, and the absence of measurable achievement indicators. The study concludes that model redesign should be directed toward pedagogical systematization, the integration of Islamic digital literacy, and the strengthening of evaluation systems based on measurable indicators in order to cultivate an “Adaptive Islamic Leader” relevant to the Society 5.0 era.